Dynamic structural property of organic-inorganic metal halide perovskite - Lee, Jin-Wook (iScience, 2020)
Unique organic-inorganic hybrid semiconducting materials have made a remarkable breakthrough in new class of photovoltaics (PVs). Organic-inorganic metal (Pb and/or Sn) halides (-I, -Br, and -Cl) are the semiconducting absorber with the crystal structure of the famous “Perovskite”. It is widely called “perovskite solar cells (PSCs)” in PV society. Now, the power conversion efficiency (PCE) of PSCs is recorded in 25.5%. Prototypical composition of the absorbers is (A = methylammonium [MA], formamidinium [FA], and Cs), (M = Pb and/or Sn), and (X = I, Br, and Cl) in the form of perovskite AMX(3). Since the report on the stable all solid-state PSCs in 2012, the average annual growth rate of PCE is well over ∼10%. Such an outstanding PV performance attracts huge number of scientists in our research society. Their chemical as well as physical properties are dramatically different from monocrystalline Si, GaAs, other III-IV semiconductors, and many oxides with the crystal structure of perovskite. In this review, different fundamental aspects, in particular, the dynamic properties of A site cationic molecules and PbI(6) octahedrons linked with their corners, from other semiconducting and dielectric materials are reviewed and summarized. Upon discussing unique properties, perspectives on the promising PV applications based on the comprehension in dynamic nature of the orientation in A site molecule and PbI(6) octahedron tilting will be given.